2008
DOI: 10.1007/s00345-008-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of sildenafil administration on testicular torsion/detorsion damage in rats

Abstract: Sildenafil administration during testicular torsion decreased ischemia/reperfusion cellular damage. The results of biochemical studies suggest that, reduction of oxidative stress by sildenafil may have a major role in its cytoprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 23 publications
6
68
0
5
Order By: Relevance
“…They reported increased levels of antioxidant enzyme levels, decreased levels of lipid peroxidation, and germ cell apoptosis. 32 Similarly protective effects of low-dose sildenafil on contralateral testis were reported in another study; 15 however, they found high-dose sildenafil had no protective effect on testis histopathologically or biochemically. In another study, vardenafil administration was found to have protective effects in rat testis after 30 minutes of torsion and four hours reperfusion.…”
mentioning
confidence: 63%
“…They reported increased levels of antioxidant enzyme levels, decreased levels of lipid peroxidation, and germ cell apoptosis. 32 Similarly protective effects of low-dose sildenafil on contralateral testis were reported in another study; 15 however, they found high-dose sildenafil had no protective effect on testis histopathologically or biochemically. In another study, vardenafil administration was found to have protective effects in rat testis after 30 minutes of torsion and four hours reperfusion.…”
mentioning
confidence: 63%
“…Similar to MDA, SOD activity reflects the oxidative stress in tissue. 12 Alternative medications that may aid in restoration of reperfusion injury after restoration have been investigated. Nevertheless, no consensus could be established on the indications, effectivity, dosage, and duration of these molecules on alleviation of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no consensus could be established on the indications, effectivity, dosage, and duration of these molecules on alleviation of I/R injury. 5,11,12 Pyrrolidine dithiocarbamate is a low-molecular weight thiol compound used as an antioxidant against the toxic impacts of free radicals. This beneficial effect of PDTC is linked with its thiol group, which acts by neutralizing reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…2,16,17 Deneysel modellerde oksijen radikal süpürücüleri gibi kimyasal ajanlar, İ/R hasarını engellemede başarılı bulunmuş, fakat ciddi yan etkileri nedeniyle bunların çok azı bu amaçla klinik kullanıma girebilmiştir. 18,19 Deksmedetomidinin testiküler İ/R üzerine olan etkilerinin araştırıldığı bu çalışmada, kolay temin edilmesi, deneysel İ/R modellerinin uygulandığı ve deksmedetomidinin antiinflamatuar etkinliğinin incelendiği çalışmalarda kullanılmış olması nedeniyle deney hayvanı olarak sıçan seçil-miştir. 2,[8][9][10] Deneysel çalışmalarda farklı torsiyon derecelerinin araştırıldığı dikkati çekmiştir.…”
Section: Discussionunclassified